2017
DOI: 10.1111/ejn.13731
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cerebellar transcranial direct current stimulation on static and dynamic postural stability in older individuals: a randomized double‐blind sham‐controlled study

Abstract: The aging population is growing rapidly. Risk of falling is higher in older people compared to young adults due to several reasons including poor posture and balance. The main aim of this study was to investigate the effect of cerebellar anodal transcranial direct current stimulation (a-tDCS) on static and dynamic postural stability in older individuals. Twenty-nine older adults participated in this study and were randomly allocated to two groups of active a-tDCS (experimental; n = 14) or sham tDCS group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 64 publications
1
44
1
Order By: Relevance
“…Most published studies used the cerebellum or primary motor cortex (M1) as the target areas for tDCS. They reported that 20 minutes of cerebellar tDCS in older adults could improve their stability indices in the anteroposterior (AP) (7,8) and mediolateral (ML) directions (8). Craig and Doumas (7) also showed that M1 tDCS with an intensity of 2 mA could decrease the peak-to-peak sway amplitude in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies used the cerebellum or primary motor cortex (M1) as the target areas for tDCS. They reported that 20 minutes of cerebellar tDCS in older adults could improve their stability indices in the anteroposterior (AP) (7,8) and mediolateral (ML) directions (8). Craig and Doumas (7) also showed that M1 tDCS with an intensity of 2 mA could decrease the peak-to-peak sway amplitude in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…After completing the full-text review, one conference abstract and one study without providing study protocol were excluded. Ten studies examining the effects of tDCS on balance and mobility in older adults with relatively healthy status or with functional impairment (e.g., stroke, slow gait) (Kaski et al, 2013;Manor et al, 2015Manor et al, , 2018Saeys et al, 2015;Zhou et al, 2015Zhou et al, , 2018Ehsani et al, 2017;Kaminski et al, 2017;Nomura and Kirimoto, 2018;Yosephi et al, 2018) were accepted to be included in the systematic review and meta-analysis. Figure 2 illustrates the results of the Cochrane risk of bias tool.…”
Section: Resultsmentioning
confidence: 99%
“…Post-stroke, postural control is likely more sensory-driven than anticipatory, as anticipatory mechanisms involve various cerebral regions, including cortical, subcortical, and subtentorial areas (Hocherman et al, 1988;Massion et al, 2004). A single session of anodal tDCS on the cerebellum improved balance and postural stability in older adults (Ehsani et al, 2017) but did not influence static postural control in young adults (Inukai et al, 2016), whereas cathodal tDCS over the cerebellum impaired static balance (Foerster et al, 2017). Additionally, with the immediate proximity of the supplementary motor area anatomically, placing the electrode over the leg motor area for tDCS stimulation could possibly result in effects in the supplementary motor area.…”
Section: Discussionmentioning
confidence: 99%